Wendt's Challenge to Social Science: Quantum Physics, Consciousness, and Society. Issue 2 (3rd April 2017) - Steinmo, Sven
ABSTRACT: Alexander Wendt's Quantum Mind and Social Science challenges social scientists to replace contemporary understandings of the individual and society with concepts better suited to quantum reality. This would mean replacing reductionist materialism with notions of consciousness as probabilistic, not strictly determined; and substituting, for individualistic models of society, new ones that acknowledged our connectedness to each other "at a distance, " i.e., without mediation by mechanisms modeled on Newtonian physics. His challenge is welcome, for in both respects, Wendt would have us replace ways of thinking that have long been inadequate to explain empirical reality.